MicroRNA-99 Family Targets AKT/mTOR Signaling Pathway in Dermal Wound Healing - Jin, Yi (Public Library of Science, 2013)
Recent studies suggest that microRNAs play important roles in dermal wound healing and microRNA deregulation has been linked with impaired wound repair. Here, using a mouse experimental wound healing model, we identified a panel of 63 differentially expressed microRNAs during dermal wound healing, including members of miR-99 family (miR-99a, miR-99b, miR-100). We further demonstrated that miR-99 family members regulate cell proliferation, cell migration, and AKT/mTOR signaling. Combined experimental and bioinformatics analyses revealed that miR-99 family members regulate AKT/mTOR signaling by targeting multiple genes, including known target genes (e.g., IGF1R, mTOR) and a new target (AKT1). The effects of miR-99 family members on the expression of IGF1R, mTOR and AKT1 were validated at both the mRNA and protein levels. Two adjacent miR-99 family targeting sites were identified in the 3′-UTR of the AKT1 mRNA. The direct interaction of miR-100 with these targeting sites was confirmed using luciferase reporter assays. The microRNA-100-directed recruitment of AKT1 mRNA to the RNAi-induced silencing complex (RISC) was confirmed by a ribonucleoprotein-IP assay. In summary, we identified a panel of differentially expressed microRNAs which may play important roles in wound healing. We provide evidence that miR-99 family members contribute to wound healing by regulating the AKT/mTOR signaling.